แนวทางการบริหารโครงการยกระดับผลสัมฤทธิ์ทางการเรียน โรงเรียนเครือข่ายที่ 55 สังกัดสำนักการศึกษา กรุงเทพมหานคร GUIDELINES FOR MANAGEMENT OF THE PROJECT TO ENHANCE STUDENTS’ ACHIEVEMENT FOR SCHOOL CLUSTER 55 UNDER BANGKOK METROPOLITAN ADMINISTRATION - รุ่งเรือง, นิรมล; เจริญกุล, นันทรัตน์ (An Online Journal of Education, 2017)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพปัญหาและนำเสนอแนวทางการบริหารโครงการยกระดับผลสัมฤทธิ์ทางการเรียน โรงเรียนเครือข่ายที่ 55 สังกัดสำนักการศึกษา กรุงเทพมหานคร กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ ผู้บริหาร หัวหน้ากลุ่มสาระการเรียนรู้ และครู โรงเรียนเครือข่ายที่ 55 จำนวน 97 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถาม มีลักษณะเป็นแบบตรวจสอบรายการ และมาตราส่วนประมาณค่า วิเคราะห์ข้อมูลโดยใช้ค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์เนื้อหา ผลการวิจัย พบว่า สภาพการบริหารโครงการยกระดับผลสัมฤทธิ์ทางการเรียน โรงเรียนเครือข่ายที่ 55 สังกัดสำนักการศึกษา กรุงเทพมหานคร ในภาพรวมตามความคิดเห็นของผู้บริหาร และหัวหน้ากลุ่มสาระการเรียนรู้ อยู่ในระดับมากที่สุด เมื่อพิจารณาเป็นรายด้าน พบว่า ด้านการประเมินผลโครงการ มีค่าเฉลี่ยสูงสุด รองลงมาคือ การดำเนินงานโครงการ และ การวางแผนโครงการ ตามลำดับ ปัญหาการบริหารโครงการ ในภาพรวม พบว่า ปัญหาการบริหารโครงการยกระดับผลสัมฤทธิ์ทางการเรียน อยู่ในระดับน้อย โดยปัญหาที่มีค่าเฉลี่ยสูงสุด คือ ด้านการวางแผนโครงการ สภาพการบริหารโครงการตามความคิดเห็นของครูในภาพรวม พบว่า อยู่ในระดับมาก รายด้านที่มีค่าเฉลี่ยสูงสุด คือ การประเมินผลโครงการ รองลงมาคือ การวางแผนโครงการ และการดำเนินงานโครงการ ตามลำดับ ปัญหาการบริหารโครงการ ในภาพรวม พบว่า มีปัญหาอยู่ในระดับน้อย โดยปัญหาที่มีค่าเฉลี่ยสูงสุด คือ ด้านการประเมินผลโครงการ แนวทางการบริหารโครงการยกระดับผลสัมฤทธิ์ทางการเรียน คือ ผู้ประสานงานโรงเรียนเครือข่าย ต้องมีการประชุมวางแผนรวมทั้งกำหนดนโยบายและแนวปฏิบัติร่วมกันระหว่างผู้บริหาร ครู พ่อแม่ ผู้ปกครองและตัวแทนชุมชนผู้ประสานงานให้ชัดเจนทั้งหมด โรงเรียนต้องมีการจัดสรรทรัพยากรอย่างเพียงพอ ครูผู้ประสานงานเครือข่ายต้องมีความชัดเจนในการสื่อสารและการดำเนินงาน The purposes of this research were to study problems and to present guidelines for management of a project to enhance students' achievement for school cluster 55 under Bangkok Metropolitan Administration. The sample population of this research were 97 respondents consisting of school directors, head teachers, and teachers of school cluster 55. The tools used in this research were a checklist and rating scaled questionnaire. The data were analyzed using frequency distribution, percentage, mean, standard deviation, content analysis. The research findings show that state of management of the project to enhance student’s achievement for school cluster 55 under Bangkok Metropolitan Administration according to comments from school directors and head teachers was overall ranked as the highest. The highest mean was evaluation, followed by implementation and planning, respectively. Overall problems in the management of the project found that the problems in the management of the project to enhance student’s achievement were at a low level. The highest mean of the problems included was the planning. The state of the management of the project from the teachers’ comments was at a high level. Evaluation had the highest mean, followed by planning and implementation, respectively. Overall problems in the management of the project were at a low level while the highest mean of the problems was the evaluation. The Guidelines for the management of the project to enhance students’ achievement were that the school cluster coordinators should have a meeting to set up clear policies and mutually agreed practice among school directors, teachers, parents, and local representatives; schools should arrange sufficient resources; and school cluster coordinators should have a clear message in communication and implementation.